Patient Preference for Antiepileptic Drugs Treatment in China: Evidence From the Discrete Choice Experiment - Hua, Yingjie; Zhu, Zhenguo; Li, Xueying; Gong, Jiaoni; Ding, Siqi; Lin, Jiahe; Wang, Xinshi; Du, Yanru; Xia, Niange; Zheng, Rongyuan; Xu, Huiqin (Frontiers in Neurology, 2020)
Objective: Explore Chinese patients' risk-benefit preferences and willingness-to-pay (WTP) for antiepileptic drugs (AEDs) treatment through the discrete choice experiment (DCE). Method: Six attributes including the efficacy of AEDs, adverse reactions (digestive system, neuropsychic systems, and the effects on the fetus), dosing frequency and drug costs (to estimate patient WTP) were included in the DCE questionnaire based on results collected from literature reviews, expert consultation, and patient survey. The alternative-specific conditional logit model was used to analyze patient preference and WTP for each attribute and its level and to assess the sociodemographic impact and clinical characteristics. Results: A total of 151 valid questionnaires were collected. The result shows that five out of the six attributes are significant, except the dosing frequency. Among the six attributes, the efficacy of AEDs (10.0; 95% CI 8.9–11.1) is mostly concerned by patients, followed by the effects of AEDs on the fetus (8.9; 95% CI 7.7–10.1), duration of side effects in the neuropsychic system (4.9; 95% CI 3.7–6.0) and adverse reactions of the digestive system (3.2; 95% CI 1.5–4.2). The patients surveyed are willing to spend ¥ 1,246 (95% CI, ¥ 632- ¥ 1,861) per month to ensure 100% seizure control, and ¥ 1,112 (95% CI, ¥ 586–¥ 1,658) to reduce the risk of the drug affecting the fetus to 3%. Besides, it was found that personal characteristics including the intention for conception and AEDs treatment regimens have statistical significance. Conclusion: Improving the drug's efficacy and reducing its side effects are predominant considerations for patients with epilepsy in China, especially for those who are concerned about the seizure control and the drug effect on the fetus. This finding is useful to physicians and can encourage shared decision-making between the patients and their doctors in the clinic.